Design and Development of Pulsincap for Chronopharmaceutical Drug Delivery of Losartan Potassium - Bojja, Ramesh; rao, R. Lakshmana; Satyanandam, R.; kishore, V.Sai (Asian Journal of Pharmaceutical Research and Development, 2014)
The aim of the present investigation is to develop a pulsatile drug delivery system based on an insoluble capsule body filled with Losartan potassium microspheres and sealed with hydrogel plug. The microspheres were prepared by Emulsification internal gelation method. The plugs of varying thickness and hardness were prepared by direct compression which was then placed in the capsule opening. The drug delivery system was designed to deliver the drug at such a time when it was needed (early hours in morning). Dissolution studies of pulsatile capsule device in media with different pH (1.2, 7.4 and6.8) showed that drug release in colon could be modulated by optimizing the concentration of polymers in the plug and also the position of plug. The study showed that, lag time prior to drug release was highly affected by the plug position. The dissolution data revealed that the plug position and the composition of plug were very important to achieve a optimum formulation. Drug– polymer interaction studies indicated no interaction or complexation in between the drug and the polymer.